2021
DOI: 10.1159/000520988
|View full text |Cite
|
Sign up to set email alerts
|

Gallbladder Neuroendocrine Tumors: Is There a Need for a Specific Approach?

Abstract: Neuroendocrine tumors (NETS) of the Gallbladder or the biliary tree are rare. Most of the current guidelines and protocols are derived from the experience of managing Lung small cell neuroendocrine carcinoma (SCNEC) or gastrointestinal (GI) NETS. But the overall outcome of Gallbladder NETS (GB NETS) seems worse than similarly staged lung NETS and adenocarcinoma of the gallbladder. This may be due to its rarity and lack of literature for a focused approach towards its treatment. Hence the need for a specificall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Owing to its low incidence and controversial clinical features, gallbladder NEN is often compared with adenocarcinoma, and several imaging features can be used to differentiate between the two 31–33 . However, different studies have arrived at different conclusions regarding the prognosis of gallbladder NEN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to its low incidence and controversial clinical features, gallbladder NEN is often compared with adenocarcinoma, and several imaging features can be used to differentiate between the two 31–33 . However, different studies have arrived at different conclusions regarding the prognosis of gallbladder NEN.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to its low incidence and controversial clinical features, gallbladder NEN is often compared with adenocarcinoma, and several imaging features can be used to differentiate between the two. 31 , 32 , 33 However, different studies have arrived at different conclusions regarding the prognosis of gallbladder NEN. Three studies, involving 10, 15, and 28 patients with gallbladder NEN, reported a worse prognosis in patients with gallbladder NEN than those with adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…But these treatment protocols lack the support of randomized large trials and hence should be cautiously used and scrutinized from time to time. [7, 11]…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis, the MINEN lesions’ median progression-free survival was 5–6 months and median overall survival was 12–18 months, which is similar to advanced carcinomas. [7, 11] In another study with MINEN patients, the overall survival was 44.5 months and median recurrence-free survival was 12.5 months. Observation to be noted in this study was the use of multimodal treatment strategy (chemotherapy ± radiotherapy) versus surgery alone that prolonged the overall survival from 75 months in the former group to 18.9 months in the latter group [18].…”
Section: Discussionmentioning
confidence: 99%
“…This pathology affects women aged in their sixties [ 14 ]. Ayabé et al [ 17 ] analyzed 754 patients with GBNEN, the majority of whom were women (69 %).…”
Section: Discussionmentioning
confidence: 99%